PERADABAN ISLAM PADA MASA DINASTI-DINASTI KECIL DI TIMUR BAGHDAD - Al Farouqy, AR MIFTAH (Rihlah: Jurnal Sejarah dan Kebudayaan, 2021)
Abstact: This article discusses the development of Islamic civilization in the east of Baghdad. The Abbasid empire once reached the peak era of Islamic civilization. This qualitative work was written by library method, the data collected by the writter of the history books. The study yileded results tht the Abbasid victory was short-lived, the dynamic polliticall situation, coupled with the power struggle between nations the Persian-Turkish and the Sunni-Shia conflict in the east region of Baghdad. The situation gave rise to a pollitical movement that resulted in new power from the Persians who founded power in the Thahirid Dynasty (820-897 c. e.), followed by The Shaffarid Dynasty (867-908 c. e), The Samanid Dynasty (819-999 c.e.), and The Buyid Dynasty (933-1055 c.e.). From Turk came the Ghaznavid Dynasty (977-1186 c.e.), The Seljuk Dynasty (1037-1157 c.e.) and The Khwarazmian Dynasty (1077-1231 c.e.). The Caliph is only symbol of the state of the Buyid-Seljuk era, and The Abbasid Empire are divided into small states led by governors known as amir or sulthan. It also gave rise the rival cities of Baghdad as the center of world civilization, such as Isfahan, Ghaznah, Shiraz and Bukhara Keywords: Abbasid, Centra Asia, Islamic Civilization, East of Baghdad Abstrak: Artikel ini membahas perkembangan peradaban Islam di Timur Baghdad. Dinasti Abbaisyah pernah mencapai era puncak peradaban Islam. Artikel yang merupakan penelitan kualitatif ini ditulis dengan metode pustaka, data dikumpulkan oleh penulis dari buku-buku sejarah. Dari penelitian ini didapatkan hasil, bahwa kejayaan Abbasiyah tidak berlangsung lama, situasi politik yang berlangsung secara dinamis, diwarnai dengan perebutan pengaruh kekuasaan antara bangsa Persia-Turki dan konflik Sunni-Syiah di wilayah timur Baghdad. Situasi ini melahirkan gerakan politik yang membuat kekuasaan baru di mulai dari bangsa Persia yang mendirikan kekuatan di Dinasti Thahiriyah (820-897 M), kemudian dilanjutkan oleh Dinasti Shaffariyah (867-908 M), Dinasti Samaniyah (819-999 M), dan Dinasti Buwaihi (933-1055). Dari bangsa Turki, berdiri Dinasti Ghaznawiyah (977-1186 M), Dinasti Seljuk (1037-1157 M) dan Dinasti Khwarizm (1077-1231 M). Khalifah hanya sebagai simbol negara di era kekuasaan Buwaihi-Seljuk, dan negara Abbasiyah terpecah belah menjadi negara-negara kecil yang dipimpin oleh para gubernur yang dikenal dengan amir atau sulthan. Selain itu, keadaan ini juga melahirkan kota-kota pesaing Baghdad sebagai pusat peradaban dunia, seperti Isfahan, Ghaznah, Syiraz dan Bukhara. Kata Kunci: Abbasiyah, Asia Tengah, Peradaban Islam, Timur Baghdad